The management of environmental taxation, ICT, and financial development over the load capacity in advanced economies - Balsalobre-Lorente, Daniel; Topaloglu, Emre E; Nur, Tugba; Pilař, Ladislav (Journal of environmental management, 2025)
The study examines the link between economic growth and environmental sustainability in advanced economies from 1994 to 2023 within the LCC (Load Capacity Curve) hypothesis framework. Additionally, the study investigates the moderating role of ICT and environmental taxes in the linkage between economic growth and the Load Capacity Factor (LCF). Second-generation panel data analysis methods, namely CUP-FM and BA-OLS techniques, were employed for coefficient estimation, and the MMQR method was applied to reveal the differing effects of variables at quantile levels. Empirical findings indicate a U-shaped link between LCF and economic growth, thereby validating the LCC hypothesis for advanced economies in the long term. Additionally, direct positive effects of ICT and environmental taxes on LCF were observed, and it was determined that the interactions between GDP and ICT, as well as between GDP and environmental taxes, are positively related to LCF. According to the MMQR analysis, the negative effect of economic growth on LCF is weaker in the lower quantiles and stronger in the higher quantiles. The impact of ICT and environmental taxes on LCF is negative in the lower quantiles and turns positive in the higher quantiles. The interaction between economic growth and ICT was positive across all quantiles, with the highest effect occurring in the 90th quantile. Similarly, the interaction between environmental taxes and economic growth was positive across all quantiles, with the most substantial impact observed in the 10th and the weakest in the 90th quantile. While the control variables of renewable energy consumption positively impact LCF in all quantiles, the effect of financial development is adverse in the lower quantiles and positive in the higher quantiles. The findings underscore the importance of integrating growth, finance, digitalization, taxation, and energy policies to safeguard environmental capacity and promote sustainability in advanced economies.
Keywords: Environmental tax; ICT; Load capacity factor; Load capacity curve; Economic growth